Moderate Islamic Boarding School Education - Ilmiah, Rikhlatul; Zaghloul, Taha Romadhan; Pristine, Depict (IJIBS, 2023)
The challenges faced by Pesantren today are not only the ability to consume all classical tradition materials but the development of modern culture and civilization has implications for socio-culture in society. The bigger challenge faced by Pesantren is openness to moderate thoughts, thinking scientifically and with a comprehensive perspective. Diniyah higher education or Ma'had Aliy provides a new pattern as Pesantren education which maintains the continuity of the tradition of classical texts while providing "wide space" for methodological studies and moderate thoughts. This paper is to provide an overview of the efforts of Ma'had Aliy Situbondo to revitalize the concept of the studies presented and held there to create moderate studies. This research uses a descriptive qualitative method. The results of this study, Ma'had Aly initiated higher education in general without losing the identity of the Pesantren materials which became its special features. The concept of manhajiy has an impact on the paradigm of moderate thinking and literacy that actualizes the interaction of theories, manuscript studies, and analyzes.